2013
DOI: 10.1080/10495398.2012.750245
|View full text |Cite
|
Sign up to set email alerts
|

IGF1mRNA Splicing Variants in Liaoning Cashmere Goat: Identification, Characterization, and Transcriptional Patterns in Skin and Visceral Organs

Abstract: Insulin-like growth factor I (IGF1) is a member of the insulin superfamily. It performs important roles in the proliferation and differentiation of skin cell and control of hair cycles and is thought to be a potential candidate gene for goat cashmere traits. In this work, we isolated and characterized three kinds of IGF1 mRNA splicing variants from the liver of Liaoning Cashmere goat, and the expression characterization of the IGF1 mRNA splicing variants were investigated in skin and other tissues of Liaoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Many studies have identified some genes associated with the growth and properties of wool fibers in sheep and goats, such as DSG1, IGF-IR, KRTAPs, ILK, as well as the KRT and KRTAP genes (Rufaut et al, 1999;Bin et al, 2006;Yu et al, 2011;Yang et al, 2012;Liu et al, 2015). In the past few decades, the regulators of cashmere fiber growth have been studied at several levels, including genes with methylation characteristics (Bai et al, 2013;Fan et al, 2015;Bai et al, 2017). Given the indispensable function of RNA m6A modification in regulating gene express and involving in various bioprocesses, it is reasonable to speculate that regulation of m6A modification might also be associated with the cashmere fineness.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified some genes associated with the growth and properties of wool fibers in sheep and goats, such as DSG1, IGF-IR, KRTAPs, ILK, as well as the KRT and KRTAP genes (Rufaut et al, 1999;Bin et al, 2006;Yu et al, 2011;Yang et al, 2012;Liu et al, 2015). In the past few decades, the regulators of cashmere fiber growth have been studied at several levels, including genes with methylation characteristics (Bai et al, 2013;Fan et al, 2015;Bai et al, 2017). Given the indispensable function of RNA m6A modification in regulating gene express and involving in various bioprocesses, it is reasonable to speculate that regulation of m6A modification might also be associated with the cashmere fineness.…”
Section: Introductionmentioning
confidence: 99%
“…The growth and regeneration of SHFs recurs annually throughout the lifetime of each goat [ 22 ]. The SHF cyclic process involves several phases of growth (early anagen, April–August; anagen, August–November), regression (catagen, December–January), and quiescence (telogen, February–March) [ 23 , 24 ]. Early studies of mouse HFs noted that the ability to propagate anagen induction is limited to early anagen follicles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the secondary follicle cycle can be divided into three periods: anagen (April–November), regression (December–January the following year), and telogen (from February to March the following year) [ 60 ]. In the anagen phase, Cashmere rapidly grows under the control of related genes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%